Impact of inclusion of hybrid red tilapia (Oreochromis mossambicus × O. niloticus), on total production in farm pond aquaculture - Sharma, Pawan Kumar; Kumar, J. Stephen Sampath; Manikandavelu, D.; Kumar, V. Senthil; Anand, S. (Indian Journal of Fisheries, 2021)
The present study was conducted to evaluate the impact of inclusion of hybrid red tilapia (Oreochromis mossambicus × O. niloticus) on productivity in carp based pond aquaculture. An experiment for a period of 270 days was conducted in two sets of earthen ponds (each of 0.132 ha size with 1.5 m depth). In Set I, five species viz. Catla catla, Labeo rohita, Cirrhinus mrigala, Ctenopharyngodon idella and Cyprinus carpio) were stocked (@13636 ha-1) in a respective ratio of 1:1:1:1:2. In Set II, hybrid red tilapia was included as additional species to other five carp species and stocked @ 13636 ha-1 in equal numbers. The seeds stocked (initial size 5-6 cm) were fed on commercial pellet feed having 20% protein, by broadcasting over the pond surface. The water quality parameters viz., temperature, pH, dissolved oxygen, alkalinity, nitrogen, phosphate and potassium remained more or less same in both the sets of experimental ponds. However fish growth parameters significantly differed in both the sets of experiments. Highest production of 2575.79±107.08 kg ha-1 was recorded in Set II followed by Set I with a production of 1894.32±428.44 kg ha-1. Tilapia stocked as an additional species provided a net estimated additional yield of 680.64 kg ha-1, which was 36.47% higher than that of Set I. The results of this study have proved significant impact of hybrid red tilapia inclusion on enhancing the net productivity. Keywords: Additional species, Farm ponds, Productivity, Red tilapia, Stocking density, Yield enhancement